Graphic Design and Education: A Systematic Review on The Evolution, Diverse Aspects, Innovations in Teaching Methods, and Interconnected Changes in Design - Ramli, Halina; Ibrahim, Norshahila; Putri Taqwa Prasetyaningrum; Saedon, Muhammad Abdul Malik (Journal of ICT in Education, 2024)
This systematic literature review aims to provide a comprehensive overview of the evolution of design education by exploring diverse aspects of graphic design, innovations in teaching methods, and interconnected changes in the field. The PRISMA model with four phases which are identification, screening, eligibility, and inclusion has been used in the search study. The review synthesizes existing research from various sources to examine the historical development, current trends, and future directions in design education. It encompasses a wide range of perspectives, including the changing landscape of graphic design, the integration of innovative teaching methods, and the impact of interconnected changes on design practices. The findings from this review aim to inform educators, practitioners, and researchers about the multifaceted nature of design education and contribute to the ongoing discourse in the field.